Life Drama of Digital News Daily Workers on YouTube Kompas.com; Fuch's Political Economy Perspective - MJ, Khairun Alfisyahri.; Eddyono, Aryo Subarkah (Lingkar Studi Komunikasi (LISKI), 2025)
In the digital era, a number of media, both television and online, use YouTube to distribute their content in order to obtain alternative income. Kompas.com does it. Its digital workforce is geared towards these targets. This research aims to find out the practices of daily digital news workers on YouTube Kompas.com. Fuchs' views on digital workers were used as the basis for the research. The research is qualitative research with data collection in the form of in-depth interviews, observations and documentation studies. Interviews were conducted with managing editors, lead video producers, producers, video journalists, and content creators. The results of this research show that digital worker practices include coercion, alienation and appropriation. In the realm of coercion, it can be seen that the work received by workers is not free from pressure and is not commensurate with the wages received. In isolation, workers feel proud to work at Kompas.com even though the salary is not commensurate with the work they carry out and their personal lives are taken away. Appropriation, content that has high views and traffic generated by digital workers will be sold by the company, but the profits obtained are only for the company.